ANALYSIS OF THE MAIN CHARACTERISTICS OF ONLINE SHOPPING AND SHOPPERS IN ROMANIA - OANA DOBRE-BARON; ALINA NIȚESCU (Annals of the University of Petrosani: Economics)
The appearance and expansion of the internet at a global level, as well as its use by an increasingly large number of individuals in the last three decades, has represented an opportunity for the retail industry. Entrepreneurs which had foreseen the potential of online sales have innovated this market, creating conditions and finding ways to attract and make loyal consumers. Their research, as well as studies made by other specialists, have sought to determine the main characteristics of consumers which choose this method to the detriment of in-store shopping or other forms of commerce without shops. Cultural mores, age, studies, easy adaptation to new technologies are just one part of the factors which influence the decision to buy online. As such, this paper explores the principal characteristics of online consumers in Romania. The analysis seeks to position Romania regarding this topic among the other EU nations, as well as with regards to the European mean, and also to capture the evolution of online commerce in the preceding years.